Analysis of nursing skill factors on patient physical rehabilitation: case study on the implementation of family-based bedside handover - Ismuntania Ismuntania; Nursalam Nursalam; Retno Indarwati; Kartika Kartika (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: This study aims to measure the influence of nursing skills on patients' physical rehabilitation by implementing PFCC-based bedside handover.